KESADARAN HUKUM PEMELIHARA REPTIL TERHADAP PERATURAN REGULASI PERLINDUNGAN SATWA (Lex Jurnalica, 2021)
AbstractThe protection of flora and fauna has been regulated in one of the international laws, the Convention on International Trade in Endangered Species of Wild Flora and Fauna (CITES) in 1973. Indonesia adopted the CITES provision by issuing Law Number 5 of 1990 on conservation of biological resources and ecosystems. Currently the implementing regulation is the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.20/MENLHK/SETJEN/KUM.1/6/2018 on Types of Plants and Protected Animals which replaces Government Regulation No. 7 of 1999 concerning the Preservation of Wild Animals and Plants. However, it turns out that the circulation of animals that are categorized as protected in the government regulations is still found around us. The purpose of this study is to find out the legal awareness of animal keepers related to the regulation of animal protection. The research method used is qualitative by using participatory observation techniques in data collection. This research was conducted from September 2020 to March 2021. The results of this study indicate that public awareness regarding the importance of maintaining the existence of protected and unprotected reptiles is still low. This is because the implementation of the government regulations in the field is still lacking, thus creating a sense of security for reptile keepers, especially protected reptiles. Keywords: legal awareness, animal protection regulations, implementation of animal protection regulations AbstrakPerlindungan jenis flora dan fauna telah diatur dalam salah satu hukum internasional yaitu Convention on International Trade in Endangered Species of Wild Flora dan Fauna (CITES) pada tahun 1973. Indonesia kemudian mengadopsi ketetapan CITES tersebut dengan mengeluarkan Undang-Undang Nomor 5 Tahun 1990 tentang Konservasi Sumberdaya Alam Hayati dan Ekosistemnya. Saat ini peraturan pelaksananya yaitu Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia Nomor P.20/MENLHK/SETJEN/KUM.1/6/2018 tentang Jenis Tumbuhan dan Satwa Dilindungi yang menggantikan Peraturan Pemerintah No. 7 tahun 1999 tentang Pengawetan Satwa dan Tumbuhan Liar. Namun, ternyata peredaran binatang yang dikategorikan dilindungi pada peraturan pemerintah tersebut masih dijumpai di sekeliling kita. Tujuan penelitian ini adalah untuk mengetahui kesadaran hukum para pemelihara binatang terkait dengan adanya peraturan perlindungan terhadap satwa. Metode penelitian yang digunakan adalah kualitatif dengan menggunakan teknik partisipasi observasi dalam pengumpulan data. Penelitian ini dilakukan dari bulan September 2020 sampai dengan Maret 2021. Hasil penelitian ini menyebutkan bahwa kesadaran masyarakat terkait pentingnya menjaga keberadaan reptil yang dilindungi maupun tidak dilindungi masih rendah. Hal ini dikarenakan pelaksanaan peraturan pemerintah tersebut di lapangan masih kurang, sehingga menimbulkan rasa aman bagi para pemelihara reptil khususnya reptil yang dilindungi. Kata kunci: kesadaran hukum, regulasi perlindungan satwa, implementasi peraturan perlindungan satwa